Bureaucratic Corruption and Service Delivery in Selected Ministries of Edo State: Descriptive Analysis - Okoh Itebite, Daniel (Universitas Negeri Surabaya, 2025)
The study explored how innovative governance mechanisms, particularly digital accountability tools and transparency-driven reforms, can mitigate bureaucratic corruption and enhance service delivery. In the beginning, the study examined how some forms of bureaucratic corruption techniques affect the general service delivery in the Edo State Civil Service. In doing so, the quantitative methodology was adopted using descriptive research design and the survey method of inquiry to elicit information from 188 participants through a structured questionnaire. Thereafter, the results obtained were analysed with frequency and simple percentage. The study revealed that embezzlement of funds negatively impacted on the quality of health care services provided by the Edo State Ministry of Health. The data demonstrated that public service fraud affected the quality of power supply through estimated bills, metering manipulations, high tariffs, and diversion of funds meant for the maintenance of power infrastructure, resulting in poor power transmission, power losses, and epileptic electricity supply. Further, the evidence proved that bribery and corrupt practices affected the quality of road infrastructure in Nigeria, and lastly, the data also validated that nepotism greatly affected the general service delivery in the Edo State Civil Service. The research work closed two empirical research gaps on bureaucratic corruption by critically investigating the effects of nepotism and bribery on general service delivery (health care services, infrastructure, education, and utilities). The study advocated for the implementation of digital innovations, including biometric attendance systems, AI-enhanced auditing, and blockchain technology in financial record-keeping within public offices. These advancements are designed to reduce the potential for malpractice while facilitating precise tracking of personnel, transactions, and government assets. Furthermore, the paper proposed that future inquiries into additional elements such as extortion, favoritism, misuse of subsidies, deliberate waste, bureaucratic corruption, and its effect on service delivery should take into account.